On Local Activity and Edge of Chaos in a NaMLab Memristor - Ascoli, Alon; Demirkol, Ahmet S.; Tetzlaff, Ronald; Slesazeck, Stefan; Mikolajick, Thomas; Chua, Leon O. (Frontiers in Neuroscience, 2021)
Local Activity is the capability of a system to amplify infinitesimal fluctuations in energy. Complex phenomena, including the generation of action potentials in neuronal axon membranes, may never emerge in an open system unless some of its constitutive elements operate in a locally-active regime. As a result, the recent discovery of solid-state volatile memory devices, which, biased through appropriate DC sources, may enter a locally-active domain, and, most importantly, the associated stable yet excitable sub-domain, referred to as Edge of Chaos, which is where the seed of complexity is actually planted, is of great appeal to the neuromorphic engineering community. This paper applies fundamentals from the theory of Local Activity to an accurate model of a niobium oxide volatile resistance switching memory to derive the conditions necessary to bias the device in the Locally-Active regime. This allows to partition the entire design parameter space into three domains, where the threshold switch is locally-passive, locally-active but unstable, and both locally-active and stable, respectively. The final part of the manuscript is devoted to point out the extent by which the response of the volatile memristor to quasi-static excitations may differ from its dynamics under DC stress. Reporting experimental measurements, which validate the theoretical predictions, this work clearly demonstrates how invaluable is nonlinear system theory for the acquirement of a comprehensive picture of the dynamics of highly-nonlinear devices, which is an essential prerequisite for a conscious and systematic approach to the design of robust neuromorphic electronics.